Data Collection in Cross-cultural Ethnographic Research. Issue 2 (May 2019) - Wutich, Amber; Brewis, Alexandra
Collecting data for cross-cultural research is time consuming and expensive. We report on techniques for efficient and effective cross-cultural data collection, drawn from 18 cross-cultural studies we conducted in 22 countries. We discuss research design, site selection and collaboration building, ethical review, cross-site protocol design, data collection pitfalls, and data quality checks.